Damage characteristics and dynamic response of the human thorax under combined shock waves and fragment loading - Ruijun Fan; Xiaofeng Wang; Haijie Li; Shaohong Wang; Aiguo Pi (Scientific Reports)
Abstract To investigate the mechanism of coupled damage in human body caused by shock waves and fragment, a finite element model of the human thorax was established. The validity of the model was verified by comparing the thorax damage data under blast and fragment. LS-DYNA finite element software was used to numerically simulate the mechanical response of the thorax under combined shock waves and fragment loading, and to analyze the effects of loading modes, mass of TNT charge, and blast distances on damage to human thoracic organs. The results indicate that the coupling damage effect of organs near the impact area is appreciable under the combined shock waves and fragment loading, and the mechanical parameters of human organs exceed the sum caused by shock waves and fragment individually. As the mass of TNT charge increased, both the peak velocity of skeletons and the stress on organs at the non-impact area under combined loading increase, whereas the effect on the peak stress in organs at the impact area of fragment is smaller and much larger than the sum of the stresses under shock waves and fragment loading alone. Meanwhile, the gap between peak stress of the same organ under combined loading and shock waves loading alone widened for different masses of TNT charge. Furthermore, the combined loading sequence of shock waves and fragment affects the mechanical response of human organs. An approach for evaluating the probability of injury under combined loading was proposed. The calculation results show that in the near field, the injury probability is more sensitive to the impulse of the shock waves.